Improving efficiency and enhancing productivity in transporting fertilizers by using conveyor belt cleaners - Mohamed Ariff, Tasnim Firdaus; Jusoh, Muhd. Fahmi Baihaqi; Parnin , Malek; Azenan, Mohd. Hanif (Trans Tech Publications, Switzerland, 2014)
Conveyor belts are used widely to carry and transport various materials ranging from fertilizers to foods items from the cargo ship to the packaging site. Spillage and carryback problems are common issues relating to transportaion of these types of materials at Malaysian ports. This leads to lots of wastage in fertilizers and food. In addition, extra manual labour work is required to shovel the spillage into the container. This raises the concern of hygiene especially when relating to food items. Furthermore, improper washing and drainage system has also lead to corrosion on the floor. This has resulted in a lot of inefficient work and lack in productivity in the material handling system. Therefore, in order to solve this problem, primary and secondary belt cleaners were designed using CATIA software. These newly improved simple and cost effective designs of the primary and secondary belt cleaners together with a spray shaft and efficient washing box were fabricated, tested and implemented successfully. The spillage was eliminated and with the new washing system, corrosion on the floor can be prevented from occuring in the future.